Asymmetric α-C(sp3)−H allylic alkylation of primary alkylamines by synergistic Ir/ketone catalysis - Li, Jianyu; Gong, Sheng; Gao, Shaolun; Chen, Jianfeng; Chen, Wen-Wen; Zhao, Baoguo (Nature communications, 2024)
Primary alkyl amines are highly reactive in N-nucleophilic reactions with electrophiles. However, their α-C−H bonds are unreactive towards electrophiles due to their extremely low acidity (p K a ~57). Nonetheless, 1,8-diazafluoren-9-one (DFO) can activate primary alkyl amines by increasing the acidity of the α-amino C−H bonds by up to 10 44 times. This makes the α-amino C−H bonds acidic enough to be deprotonated under mild conditions. By combining DFO with an iridium catalyst, direct asymmetric α-C−H alkylation of NH 2 -unprotected primary alkyl amines with allylic carbonates has been achieved. This reaction produces a wide range of chiral homoallylic amines with high enantiopurities. The approach has successfully switched the reactivity between primary alkyl amines and allylic carbonates from intrinsic allylic amination to the α-C−H alkylation, enabling the construction of pharmaceutically significant chiral homoallylic amines from readily available primary alkyl amines in a single step. Primary alkyl amines are highly reactive in N-nucleophilic reactions with electrophiles but their α-C–H bonds are unreactive towards electrophiles due to their extremely low acidity. Combining 8-diazafluoren-9-one with an iridium catalyst, the authors demonstrate direct asymmetric α-C-H alkylation of unprotected primary alkyl amines with allylic carbonates.